Islamic Educational Quality in Digital Religious Literature: A Content Analysis of the Websites of Islamic Educational Institutions in Indonesia - Dian Dian; Muhammad Haikal; A Rusdiana; Muhamad Luqman Nuryana; Wafiq Fadhilah Anwar (Jurnal Lektur Keagamaan, 2026)
This article examines how Islamic educational quality is constructed in the digital religious literature of Islamic educational institutions in Indonesia. Rather than evaluating institutional performance outcomes, this study examines how quality is defined, legitimized, and represented through official institutional website texts. Although studies on digital religion, Islamic educational transformation, and institutional quality have developed significantly, limited attention has been given to official websites of Islamic schools and pesantren as religious-literary texts that shape public meanings of Islamic education. Using a qualitative design with digital textual analysis and thematic content analysis, this study examines 26 website texts from seven Islamic educational institutions collected between January and March 2026. The corpus includes vision and mission statements, institutional profiles, principals’ messages, flagship program descriptions, tahfiz and tahsin narratives, and routine religious activity pages. The findings show that Islamic educational quality is constructed through three interconnected textual operations: integration, metrification, and habituation. Integration appears in the fusion of academic competence, Qur’anic achievement, moral character, leadership, and social usefulness. Metrification appears in measurable Qur’anic indicators such as 30 juz, 3 juz, 7 juz, juz 30, tahsin, and tasmi’. By repositioning institutional websites as digital religious literature, this article shows that these texts do not merely report educational programs but actively produce Islamic educational quality as a normative public discourse